Non-perturbative electroweak-scalegenesis on the test bench of dark matter detection - Kubo, Jisuke; Soesanto, Qidir Maulana Binu; Yamada, Masatoshi (The European physical journal. C, Particles and fields, 2018)
We revisit a recently proposed scale invariant extension of the standard model, in which the scalar bi-linear condensate in a strongly interacting hidden sector dynamically breaks scale symmetry, thereby triggering electroweak symmetry breaking. Relaxing the previously made assumption on U(Nf)U(Nf)U(N_f) flavor symmetry we find that the presence of the would-be dark matter candidate opens a new annihilation process of dark matter at finite temperature, such that the model can satisfy stringent constraints of the future experiments of the dark matter direct detection.